2017
DOI: 10.1002/ajpa.23264
|View full text |Cite|
|
Sign up to set email alerts
|

Resolving relationships between several Neolithic and Mesolithic populations in Northern Eurasia using geometric morphometrics

Abstract: The obtained results are discussed in application to relationships between particular groups. Unlike the Ukrainian Mesolithic, the Yuzhny Oleni Ostrov Mesolithic displays a high morphological affinity with several groups from Northern Eurasia of both European and Asian origin. A possibility of a common substrate for the Yuzhny Oleni Ostrov Mesolithic and Siberian Neolithic groups is reviewed. The Siberian Neolithic is shown to have morphological connection with both modern Siberian groups and the Native North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Current patterns of modern human craniofacial diversity evolved by a combination of both neutral and selective processes. Connections between craniofacial morphology, climate, as well as genetic and geographical similarities have long been investigated by various multivariate statistical approaches [1][2][3][4][5][6][7][8][11][12][13] . Several of these studies indicated that the neurocranium and upper face partly track neutral genetic and molecular distances, while midfacial shape also reflects climate 3,11 .…”
Section: Modern Population Evidence Of Craniofacial Diversitymentioning
confidence: 99%
“…Current patterns of modern human craniofacial diversity evolved by a combination of both neutral and selective processes. Connections between craniofacial morphology, climate, as well as genetic and geographical similarities have long been investigated by various multivariate statistical approaches [1][2][3][4][5][6][7][8][11][12][13] . Several of these studies indicated that the neurocranium and upper face partly track neutral genetic and molecular distances, while midfacial shape also reflects climate 3,11 .…”
Section: Modern Population Evidence Of Craniofacial Diversitymentioning
confidence: 99%